Gyrosigma fasciola Griffith et Henfrey ... - Al-Handal, Adil Y.; Torstensson, Anders; Wulff, Angela (Zenodo, 2022)
Gyrosigma fasciola (Ehrenberg) Griffith et Henfrey (Figure 80) Literature: (Al-Handal and Wulff 2008a, p. 54, figs. 101, 130– 131; Krammer and Lange-Bertalot 1986, p. 300, fig. 116.6). Description: Length 97–140 µm, width 11–14 µm, transverse striae 21–24 in 10 µm. Remarks: One of the most common benthic diatoms in Potter Cove. It forms a thick diatom film in some places. Ecology and distribution: A marine and brackish-water species of worldwide distribution but more frequent in the marine littoral of the Atlantic and the North Sea (Jahn et al. 2005). Reported from the Arctic (Cardinal et al. 1986; von Quillfeldt 2000). Common in Potter Cove. ... : Published as part of Al-Handal, Adil Y., Torstensson, Anders & Wulff, Angela, 2022, Revisiting Potter Cove, King George Island, Antarctica, 12 years later: new observations of marine benthic diatoms, pp. 81-103 in Botanica Marina (Warsaw, Poland) (Warsaw, Poland) 65 (2) on page 94, DOI: 10.1515/bot-2021-0066, http://zenodo.org/record/11000147 ...